Three levels of discrepancies in the records of trial sites in India, registered with the European Union Clinical Trials Register - Samanta, Anwesha Dhal; Borah, Rishima; Saberwal, Gayatri (Frontiers in Medicine, 2024)
Introduction: Clinical trial registries serve a key role in tracking the trial enterprise. We are interested in the record of trials sites in India. In this study, we focused on the European Union Clinical Trial Registry (EUCTR). This registry is complex because a given study may have records from multiple countries in the EU, and therefore a given study ID may be represented by multiple records. We wished to determine what steps are required to identify the studies that list sites in India that are registered with EUCTR. Methods: We used two methodologies. Methodology A involved downloading the EUCTR database and querying it. Methodology B used the search function on the registry website. Results: Discrepant information, on whether or not a given study listed a site in India, was identified at three levels: (i) the methodology of examining the database; (ii) the multiple records of a given study ID; and (iii) the multiple fields within a given record. In each of these situations, there was no basis to resolve the discrepancy, one way or another. Discussion: This work contributes helps to provide methodologies for more accurate searches of trial registries. It also adds to the efforts of those seeking transparency in trial data.